Abrupt Fen-Bog Transition Across Southern Patagonia: Timing, Causes, and Impacts on Carbon Sequestration - Loisel, Julie; Bunsen, Michael (Frontiers in Ecology and Evolution, 2020)
Fens and bogs are distinct in terms of their biogeochemistry, water table behavior, and net peat-accumulation regimes. While most peatlands start developing as fens, a large fraction of them eventually shift to bogs in a step-like ecosystem shift. This transition has traditionally been assumed to be primarily controlled by the ecosystem itself (autogenic control). Here we use 90 peat profiles from southernmost South America (SSA) as a case study that illustrates a synchronous, regional-scale shift from fen to bog around 4200 years ago. In light of these results, we propose and discuss conceptual models that link environmental change (allogenic control) as a trigger to the fen-bog transition (FBT). In addition, our stratigraphic analyses show that Sphagnum deposits are associated with greater peat masses, larger soil-carbon stocks, and higher rates of peat-carbon accumulation than their non-Sphagnum counterparts, with Sphagnum bogs being characterized by soil-carbon densities over twice that of non-Sphagnum peatlands (medians = 141 vs. 56 kgC/m2). Since fens and bogs also behave differently in terms of their carbon exchanges with the atmosphere, a better appraisal of the processes involved in the FBT could help elucidate the role of this critical ecosystem shift in the past and future global carbon cycle.